Scripta: Developing an Innovative Educational Play Tool to Boost Early Childhood Reading Literacy - Ath Thahirah, Khadijah; Priyanti, Nita; Patilima, Hamid (Journal of Islamic Education Students (JIES), 2025)
This study aims to develop and assess the feasibility of the Scripta educational play tool to enhance early reading literacy among young children age 5-6 years old. Using the R&D method with the ADDIE model, the study followed the stages of needs analysis, design, development, implementation, and evaluation. The initial product, consisting of illustrated cards, was validated by material experts, media experts, and early childhood practitioners, yielding an average score of 81.5 (“Feasible”). Practicality testing by teachers resulted in an average score of 85.8 (“Highly Practical”). A limited trial involving 12 children showed significant improvement, shifting from predominantly low pre-test scores to high and very high post-test scores. The findings demonstrate that Scripta effectively improves letter recognition, vocabulary mastery, and reading interest through play-based learning. The study highlights the importance of integrating culturally grounded and Islamic value–based interactive media to strengthen early childhood literacy and provide practical benefits for teachers and schools.